Stressed by your job: What is the role of personnel policy? - Elena Shvartsman; Michael Beckmann (Deutsches Institut für Wirtschaftsforschung (DIW), 2015)
Work-related stress can lead to substantial health problems and thereby result in immense costs for establishments. Therefore, the question as to what extent establishments contribute to their employees' stress levels is of great importance for firm performance. We investigate the relationship between personnel policies and work-related stress by considering a series of personnel policies that refer to a worker's job reward, job demand, or job control situation. Using data from the German Socio-Economic Panel (SOEP) we find statistically significant associations of several policies and work-related stress. Most importantly, bad promotion opportunities and low working time control turn out to be associated with higher stress levels, while the opposite is true for an adequate salary.
Keywords: I10; J81; M54; 330; job stress; personnel policy; working conditions